The Nursing Interventions for Smoking Cessation in a Hospital Setting - Tahlil, Teuku (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
The Nursing Interventions for Smoking Cessation in a Hospital Setting